Lived Experiences of Filipino Mothers with Multiple Miscarriages - Bergonio, Kristine; Bergonio, Kristine R; Bellen, Princess Diana Rose G.; Timajo, Dan Adrian T.; Bergonio, Elvin R. (Alta Dharma Publisher, 2025)
Background: The emotional and psychological recovery processes of Filipino mothers who have experienced multiple miscarriages are inadequately understood, particularly within the Philippine public health care system. Objective: The study aims to understand the lived experiences of Filipino mothers who have suffered multiple miscarriages, focusing on their emotional and psychological recovery. Method: Utilizing a phenomenological research design, in-depth interviews were conducted with 12 mothers from rural areas in the Philippines. Result: The study identified several themes, including the varied grieving and recovery processes, the presence of misinformation, poor health-seeking behavior, and the significant role of family support. It also highlighted gaps in the Philippine healthcare system, such as the absence of specialized programs for miscarriage care and limited access to essential prenatal services like ultrasounds. Conclusion: The findings underscore the need for improved public health initiatives, including education campaigns to address misinformation, specialized training for healthcare providers, and the establishment of support programs tailored to women who experience miscarriages. Recommendation: It include legislative action to ensure better care for women facing miscarriages, enhanced community-based support, and the provision of free ultrasound services in rural health units. This study emphasizes the importance of culturally sensitive interventions to improve the health and well-being of Filipino mothers coping with the emotional and psychological impact of multiple miscarriages. The study recommends legislative action for improved miscarriage care, community-based support, and free rural ultrasound services, highlighting the need for culturally sensitive interventions to support Filipino mothers' emotional and psychological well-being after multiple miscarriages